2019
DOI: 10.1016/j.cplett.2019.05.052
|View full text |Cite
|
Sign up to set email alerts
|

I2O in solution and volatility

Abstract: I 2 O can be prepared in 96% sulfuric acid and extracted in chlorinated solvents.• UV-vis spectra are presented in DCM and CCl 4 .• These solutions offer new methods for studies of the I(+1) properties.• I 2 O forms an ionic complex in acetonitrile preserving the I(+1) oxidation sate.• I 2 O is a volatile compound with consequences in atmospheric chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The difficulty of studying these mechanisms is increased by the fact that some intermediates have only been recently detected (for example, before mentioned I 2 O). 45 One can assume that the mechanisms of the redox reactions are particularly complex. On the other hand, it has been lately reported that the oxidation reactions between organic compounds and free radical intermediates occur via hydrogen atom transfer (HAT) mechanism.…”
Section: Figurementioning
confidence: 99%
“…The difficulty of studying these mechanisms is increased by the fact that some intermediates have only been recently detected (for example, before mentioned I 2 O). 45 One can assume that the mechanisms of the redox reactions are particularly complex. On the other hand, it has been lately reported that the oxidation reactions between organic compounds and free radical intermediates occur via hydrogen atom transfer (HAT) mechanism.…”
Section: Figurementioning
confidence: 99%